2020
DOI: 10.1016/j.ihj.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Implication of d-dimer in rheumatic severe mitral stenosis – A tertiary centre study

Abstract: Background In rheumatic mitral stenosis (MS), left atrial (LA) thrombus and LA spontaneous echo contrast (LA SEC) reflect hypercoagulability. The study focuses on whether D-dimer levels predict the existence of LA thrombus and SEC in patients with severe MS. Methods 95 consecutive patients with severe MS referred for transesophageal echocardiogram (TEE) between July 2011 and March 2012 to evaluate LA thrombus prior to balloon mitral valvotomy (BMV) were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This finding is similar to that of Sukulal et al, (2020), which showed there is significant association of AF with LA thrombus. 10 Among other clinical parameters, NYHA class was higher in group I than group II. Majority of patients of group I were in NYHA class III (64%), while majority were in NYHA class II (56%) in group II, this was statistically significant (p<0.05).…”
Section: Discussionmentioning
confidence: 91%
“…This finding is similar to that of Sukulal et al, (2020), which showed there is significant association of AF with LA thrombus. 10 Among other clinical parameters, NYHA class was higher in group I than group II. Majority of patients of group I were in NYHA class III (64%), while majority were in NYHA class II (56%) in group II, this was statistically significant (p<0.05).…”
Section: Discussionmentioning
confidence: 91%